Water footprint assessment in expressway infrastructure system. (20th January 2021) - Kim, Young Woon; Hwang, Yong Woo; Jo, Hyun Jung; Kim, Junbeum
Abstract: The water footprint is a useful and important method for calculating water consumption in products and systems. Up to date, many studies on water footprints have focused on the high water consumption sectors of agriculture and livestock products, but few have looked at social infrastructure. The aim of this study is to calculate the water footprint using previous water footprint evaluation methodologies for the expressway infrastructure system and compare the results of each different methodology used for expressway infrastructure systems. Boulay's methodology, the Ministry of Environment's methodology using Ecoinvent, and Ministry of Environment's methodology using Korean life cycle inventory were used and compared. As a result, 58, 801 m 3 H2 Oeq of direct and indirect water was used for 1 km expressway with Boulay method, also 42, 030 m 3 H2 Oeq, and 27, 485 m 3 H2 Oeq, of direct and indirect water was consumed using Ministry of Environment's methodology using Ecoinvent and Ministry of Environment's methodology using Korean life cycle inventory. The study approach and results can support for more sustainable water management in infrastructure system. Highlights: Three water footprint methods were assessed and compared. Water footprint were calculated for the expressway infrastructure system. For 1 km expressway, 58, 801 m 3 H2 O eq. direct and indirect water was used (Boulay method). Other two methods showed 42, 030 m 3 H2 O eq. and 27, 485 m 3 H2 O eq. water footprint.